Pragmatism - Malachowski, Alan R.; Sage eBooks (London : SAGE, 2004)
The dramatic resurgence of American Pragmatism was one of the most important intellectual developments in the Twentieth Century. These volumes include all the relevant material to assess the origins and revival of Pragamatism in the works of Charles Peirce, William James, Richard Rorty, Hilary Putnam and others.
v.1. The historical development of pragmatism -- v. 2. The revival of pragmatism -- v.3. Critical responses.
Specialized.
Description based on print version record.
Includes bibliographical references.
Keywords: Pragmatism; Electronic books